Interactive processes of Europeanization: a case of civil society in Turkey - Çetin, Eylül (My University, 2018)
1980’li yıllardan beri, Türkiye’deki sivil toplum, çeşitli iç ve dış gelişmelere bağlı olarak ciddi bir gelişme kaydetmiştir. Ancak, 1999 yılında Türkiye’nin adaylığının resmi olarak tanınmasıyla başlayan Avrupa Birliği katılım süreci, Türkiye’deki yasal ve kurumsal yapıyı sivil toplumun işleyişi açısından iyileştirmekle kalmayıp, sivil toplum kuruluşlarının faaliyetlerini de önemli ölçüde geliştirmiştir. Bu bağlamda, AB’nin Türkiye’de sivil toplumun geliştirilmesi ve güçlendirilmesine dahil olması, Avrupalılaşma süreçlerinin interaktif mekanizmalarının doğrudan ve dolaylı yollarıyla gerçekleşmektedir. Koşulluluk ilkesi, finansman politikaları ve mekanizmaları, etkileşimler, ağlar ve ortaklıklar yoluyla tesis edilen işbirliği ve Türkiye’de sivil faaliyetlerin meşrulaşması, interaktif Avrupalılaşma süreçlerinin Türk sivil toplumunun yasal ve pratiksel açılardan gelişmesindeki etkilerinin anlaşılmasına yönelik kategorilerdir. Bu tez çalışması, Avrupalılaşma perspektifinin yukarıdan aşağıya ve aşağıdan yukarıya doğru çözümlemelerini yaparak Türkiye’nin Avrupalılaşmasının sonuçlarını, AB katılımı sayesinde, hem AB’nin hem de Türk sivil toplumunun birlikte şekillendirdiğini ortaya koymaya çalışmaktadır.

Since 1980s, civil society in Turkey has shown drastic advancement related to several internal and external developments. However, it is the European Union accession process began with the official recognition of Turkey’s candidacy in 1999 has significantly not only improved the Turkish legal and institutional structure for the operation of civil society but also enhanced the practices of civil society organizations in Turkey. In this regard, the involvement of the EU in the civil society development and empowerment in Turkey has been taking place through the interactive mechanisms of Europeanization processes via direct and indirect ways. Conditionality principle; funding policies and mechanisms; cooperation through interactions, networks and partnerships; legitimization of civic activity in Turkey are the categories for figuring out the influence of the interactive Europeanization processes on the development of Turkish civil society in legal and practical terms. By incorporating the top down and the bottom up considerations of Europeanization perspective into the analysis, the thesis attempts to reveal that both the EU and Turkish civil society have shaped Turkey’s Europeanization outcomes collectively thanks to the EU accession context.
Keywords: Associations, institutions, etc; Avrupa; Avrupa Birliği; Avrupa Birliği Ülkeleri; Avrupalılaşma; Civil society; Civil Society Organizations; Dernekler, kurumlar, vb; Dış ilişkiler; Europe; European Union; European Union Countries; Europeanization; Foreign relations; Non-governmental organizations; Sivil toplum; Sivil Toplum Kuruluşu/ Örgütü; Sivil toplum örgütleri; Turkey; Türkiye; Türkiye Civil Society